64. studentská vědecká konference Program a sborník abstraktů - Jurajda, Michal (Masaryk University Press, 2020)
Title in English: The 64th Student Scientific Conference. The publication contains overview of lectures presented at the 64th Student Scientific Conference, organised by the Faculty of Medicine, MU on 11 November 2020.